Characteristics of a resilient leader of a humanitarian organization - Olga A. Plyushcheva; Alexander V. Makhnach (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Under the influence of ecological, economic, political and other changes, organizations, employees and their leaders inevitably and regularly face impacts that are reflected in the experience of uncertainty about their future prospects. To resist these crises, rebuild and develop, organizations must form resilient leaders and employees. The development of resilient leaders increases the ability to positively influence the entire staff of the organization and becomes their strategic advantage in overcoming difficult periods. We are convinced that such development of resilient leadership should be selected specifically for each organizational environment, its features and tasks. In this regard, the purpose of our research was to study such characteristics of the leaders of the organization that employees define as resilience and whether the subjective perceptions of employees can contribute to the choice of methods to strengthen the resilience of the organization. The empirical study involved specialists of a non-profit organization performing professional duties of staff and volunteers (N = 106, men 7.5%, women 92.5%, average age 36.7). Content-analysis was used as a research method. The results showed that the study of the characteristics of the subjective perceptions of the organizations employees about the characteristics of the resilience of their leaders can form an idea of which areas of leadership strategies require changes, which are sufficiently resourceful and can be used to select support measures, which will contribute to the targeted and specific assistance required by the organization to strengthen its resilience and the resilience of its employees. Further research in this area will be useful for a deeper understanding of the phenomenon of professional resilience and can be applied for practical purposes to manage professional resilience to help organizations and professionals overcome crises, recover and continue their development.